Uma análise da evoluç\~ao e da eficiência na agropecuária da Amazônia legal e suas consequências sobre o desmatamento na regi\~ao - Caio Rodrigues Gomes Leite; Alexandre Marinho; Antonio Salazar P. Brand\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The study analyzed the growth of agricultural activity in the Amazon region and the consequent increase in deforestation. In addition, it was investigated whether the difference in land productivity observed in agriculture in the region of the Legal Amazon can be justified by low efficiency and, for that purpose, the agricultural efficiency of the municipalities in the region was measured in comparison with the other in Brazil, and deforestation was used as an undesirable output. Therefore, it was used the data of Agricultural Census (2006) of 3,520 municipalities in Brazil with fifteen variables: thirteen inputs: crop and pasture area, labor, and the following expenditure items: fertilizers, pesticides, soil amendments, seeds and seedlings, bags and packaging, pesticides, medicines for animals, salt and animal feed, transport, electricity, fuels, a desirable output (production value) and an undesirable output (deforestation). We used the following models: the Data Envelopment Analysis - DEA model (considering variable returns of scale with input orientation), the bad output model and the Stochastic Frontier Analysis - SFA model. The results showed that municipalities with a high level of deforestation presented a positive correlation between deforestation and efficiency, suggesting that when deforestation is increased, the efficiency also increases. Municipalities with low deforestation level showed a negative correlation, indicating that those that no longer deforest, or deforest less, have fewer incentives to deforest. In addition, municipalities in the Legal Amazon showed, on average, lower efficiency compared to other Brazilian municipalities.
Keywords: Q01; Q12; C61; C67; D24; D61; 330; Legal Amazon; agriculture; deforestation; DEA; Data Envelopment Analysis; SFA; stochastic frontier analysis